Candidate proteins interacting with cytoskeleton in cells from the basal airway epithelium in vitro - Olatona, Olusola A.; Choudhury, Sayantan R.; Kresman, Ray; Heckman, Carol A. (Frontiers in Molecular Biosciences, 2024)
Introduction: The cytoskeleton consists of actin, microtubules, septins, and intermediate filaments and, in most cells, is anchored to an extracellular matrix. Each cell has a unique arrangement of this network and readjusts it from time to time. To investigate the regulation of these reorganizations, we identified interactors from extracts of four cultured lines representing basal cells from the airway epithelium. Methods: After immunoprecipitation with an antibody against keratin 17, samples were processed by liquid chromatography and tandem mass spectrometry. Samples not undergoing antibody-mediated capture were processed in parallel. Results: The main keratins of basal cells, namely Krt14 (type I) and Krt5 (type II), constituted 67% of the total keratin recovered. Several other intermediate filament proteins, nestin, lamin-B1, and prelamin A/C, were present but not enriched upon immunoprecipitation. Although the class of armadillo-repeat proteins was represented by beta-catenin1 and plakoglobin, other desmosome plaque constituents were absent. Large cytolinkers were represented by the spectraplakin, microtubule-actin cross-linking factor (Macf1), which was enriched by immunoprecipitation, and the plakin, plectin, which was not enriched. Subunits of actin filaments and microtubules, along with numerous proteins associated with them, were recovered in both immunoprecipitated samples and those lacking the capture step. Coefficients of determination were computed based on abundance. The actin-associated proteins, alpha-spectrin and brain-specific angiogenesis inhibitor (Baiaip2l), were modestly correlated with keratin abundance but highly correlated with one another and with the keratin-binding protein, annexin A2. This interaction network resembled the pedestal formed by pathogenic Escherichia coli. Microtubule-associated proteins, dynamin 1-like protein and cytoplasmic dynein 1 heavy chain (Dync1h1), were enriched by immunoprecipitation, suggesting association with keratins, whereas kinesin-1 heavy chain and microtubule-associated protein retinitis pigmentosa 1 (EB1), were not enriched. Dync1h1 abundance was negatively correlated with that of all the septins, suggesting resemblance to a known antagonistic septin-dynein 1 relationship on microtubules. Conclusions: The cell lines showed remarkable uniformity with respect to the candidates interacting with cytoskeleton. The alpha-spectrin-Baiap2l network may link actin filaments to keratin precursor particles. A smaller interaction network centered on Dync1h1 was negatively correlated with all spectrin-Baiap2l constituents, suggesting that it and its binding partners are excluded from the pedestal-like domain.